Susceptibility of human immunodeficiency virus type 1 replication in vitro to acyclic adenosine analogs and synergy of the analogs with 3'-azido-3'-deoxythymidine. - Smith, M S (1989)
The replication of human immunodeficiency virus in vitro is inhibited by some acyclic adenosine derivatives, such as 9-(2-phosphonylmethoxyethyl)adenine (PMEA) and (S)-9-(3-hydroxy-2-phosphonylmethoxypropyl)-2,6-diaminopurine [(S)-HPMPDAP], as well as by 3'-azido-3'-deoxythymidine (AZT). In a human T-lymphocyte cell line, C3, at 6 days postinfection, the 50% effective concentration (EC50) of AZT was 0.02 microM and the 90% effective concentration (EC90) was 0.33 microM; for PMEA, the EC50 was 1.9 microM and the EC90 was 27 microM. For (S)-HPMPDAP, the EC50 was 2.3 microM and the EC90 was 36 microM. Most combinations of AZT and PMEA produced a synergistic effect. In the T-cell line C3, the combination indices for 50 to 90% inhibition of virus replication ranged from 0.25 to 1.25. Combinations of PMEA (or other members of this group) with AZT appear to be worth further study for the possible treatment of acquired immunodeficiency syndrome.